'Structure' density, area, and volume as complementary tools to understand Maya Settlement: An analysis of lidar data along the great road between Coba and Yaxuna. (February 2020) - Stanton, Travis W.; Ardren, Traci; Barth, Nicolas C.; Fernandez-Diaz, Juan C.; Rohrer, Patrick; Meyer, Dominique; Miller, Stephanie J.; Magnoni, Aline; Pérez, Manuel
Highlights: Analyses of volume, basal area, and structure count (polygon) density are similar at the macro-regional scale. Structure volume and basal area densities vary from polygon densities at the site-level scale. The intersite causeway from Coba to Yaxuna was an attractor of settlement in the area of state expansion. Abstract: In this paper we present an analysis of lidar data along Sacbe 1, the longest causeway in Mesoamerica, connecting the sites of Coba and Yaxuna. In addition to performing an analysis of the density of polygons (utilized as a proxy for structures), we calculate the density of basal area and construction volume of the raised features seen in the data set. The results indicate that Maya sites in this region were fairly discrete and that the causeway was built to incorporate previously existing settlements dating prior to the period 600–700 CE. Further, the causeway was an attractor of settlement in the area of state expansion.